The Effect Of Compensation, Empowerment, And Job Satisfaction On Employee Loyalty - A, Onsardi; Thamrin Abdullah, Moch. Asmawi, (International Journal of Scientific Research and Management (IJSRM), 2017)
The purpose of this research is to analyze the direct influence of compensation, empowerment, and job satisfaction to employee loyalty, to analyze direct influence of compensation and empowerment to job satisfaction, to analyze direct influence of empowerment to job satisfaction and to analyze the direct influence to compensation to empowerment. This is a quantitative research using survey method, and the data analysis is path analysis. The conclusion of this research shows that there is direct positive influence of compensation, empowerment, and job satisfaction to employee satisfaction. There is a direct positive influence of compensation and empowerment to job satisfaction. There is a direct positive influence of compensation to empowerment.